Vedere con il disegno, or Art is Made With the Eyes (diségno, 2025)
The title of this book is a synesthesia. It makes you think of a text based on the suggestions that art, by its nature, is called to evoke. Manfredo Massironi was a visual artist –or rather: a ‘visual operator’, as he defined himself– who never loved conventions. We would not expect methodical writing from one of his books. On the contrary, he follows the artists (Paul Klee, Vasilij Kandinskij, György Kepes, among others) who, when writing about visuality, adopt a scientific rigor. [read more]